Factor of values influencing mind virtue of Muslim Malay youth: Study in Klang valley, Malaysia - Jawiah D.; Siti Masliah M.N.; Fariza M.S.; Mastor K.A.; Siti Rugayah H.T.; Adawiyah I.; Al Adib S.; Jalil M.H.; Noor Aziah M.A. (Sakarya University, 2024)
Indexed by SCOPUS